(untitled) (Global Journal of Science Frontier Research, 2012)
The study examined the extent to which some socio-demographic factors (gender, age, marital status, occupation, family size, socio-economic background and location (study area) determined public perception of water distribution problems in Iju-Ishaga, a suburb of Lagos. It used 240 respondents (128 males and 112 females) spread across the six wards in the town. Data collection involved the use of questionnaires while multiple regression was used in data analysis. The results showed that 5.6% of variation in public perception of water distribution problems could be attributed to the effect of the socio-demographic variables. Age, gender, marital status, occupation and socio-economic background were significant contributors to the prediction. The results raises critical issues for the effective distribution of public water in Iju-Ishaga. The paper concluded that public water supply can be better enhanced in Iju-Ishaga if there issues are given utmost consideration by agencies responsible for the provision of potable water.